Embracing Cooperative Learning for Critical Thinking and Enhanced Learning Outcomes - Harianto, Bambang Bagus (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to investigate the effectiveness of the Cooperative Learning approach in improving students' critical thinking and learning outcomes. Critical thinking is a core skill required for effective learning, yet many students struggle to develop this ability. The Cooperative Learning approach has been recognised as effective in improving engagement, collaboration and understanding of concepts in learning. However, research specifically exploring the impact of the Cooperative Learning approach on critical thinking and learning outcomes is limited. This research used a qualitative desk study approach to investigate the role of Cooperative Learning in improving critical thinking and learning outcomes. An in-depth literature review was conducted to gather evidence from various previous studies relevant to this topic. The results showed that the Cooperative Learning approach has a positive impact in improving students' critical thinking. Through collaboration between students, group discussions, and task-based learning experiences, students can significantly develop their critical thinking skills. In addition, the improvement of critical thinking also contributes to the improvement of overall learning outcomes. In conclusion, the Cooperative Learning approach can be an effective strategy in improving students' critical thinking and learning outcomes. The implications of this study highlight the importance of strengthening the Cooperative Learning approach in the context of learning in educational institutions.